CD4-CD8 differentiation in the thymus: connecting circuits and building memories - Xiong, Yumei (2012)
The proper choice of the CD4-helper or CD8-cytotoxic lineages by developing T cells is crucial for the generation of an antigen-responsive and functionally fit T cell repertoire. Here we present a brief overview of the transcriptional control of this process, with emphasis on two issues. The study of Cd4 expression, that had previously generated important paradigms for transcriptional regulation in eukaryotic cells, now brings new twists to the concept of ‘epigenetic memory’. On the other hand, connections are emerging between transcriptional regulators critical for commitment to either lineage. The present review attempts to integrate these findings and discusses the still elusive mechanisms that match CD4-CD8 lineage differentiation to MHC specificity.